Electrolytic capacitors

The electrolytic capacitor design with a roughened cathode foil and inorganic conductive layer, combined with controlled moisture in the electrolyte, addresses the challenge of high capacity and low ESR, enhancing adhesion and reducing leakage current.

JP7607224B2Active Publication Date: 2024-12-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023017660
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-05-28
Filing Date
2023-02-08
Publication Date
2024-12-27
Estimated Expiration
2036-03-10

AI Technical Summary

Technical Problem

Existing electrolytic capacitors face challenges in achieving high capacity while maintaining low Equivalent Series Resistance (ESR) and suppressing leakage current, particularly when using a conductive polymer layer and an electrolytic solution, due to insufficient adhesion and repairability of the carbon-containing layer on the cathode.

Method used

The electrolytic capacitor design includes a cathode foil with a roughened surface and an inorganic conductive layer having convex and concave portions, where the conductive polymer layer contacts the convex portions and the electrolyte enters the concave portions, with a controlled moisture content in the electrolytic solution to enhance adhesion and reduce ESR.

Benefits of technology

This design achieves low ESR and leakage current while ensuring high capacity, even under prolonged use, by improving adhesion between the conductive polymer and inorganic conductive layers, and stabilizing the electrolyte properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607224000002
    Figure 0007607224000002
  • Figure 0007607224000003
    Figure 0007607224000003
  • Figure 0007607224000001
    Figure 0007607224000001
Patent Text Reader

Abstract

In electrolytic capacitors that use electrolyte, this technology suppresses increases in ESR and reduces leakage current while ensuring high capacitance. [Solution] The disclosed electrolytic capacitor includes a capacitor element and an electrolyte. The capacitor element includes an anode foil having a dielectric layer formed on its surface, a cathode foil, and a conductive polymer layer. An inorganic conductive layer is formed on the surface of the cathode foil, and the inorganic conductive layer has protrusions and recesses on its surface. First regions where the inorganic conductive layer and the conductive polymer layer are in contact with each other are formed on the protrusions, and second regions where the electrolyte solution has entered between the inorganic conductive layer and the conductive polymer layer are formed on the recesses. The electrolyte contains a first solvent and 0.1 to 6.0 mass % water. The first solvent has no boiling point or a boiling point of 180°C or higher. The inorganic conductive layer contains at least one conductive material selected from the group consisting of conductive carbon, nickel, conductive nickel alloys, conductive nickel compounds, titanium, conductive titanium alloys, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor including a capacitor element having a conductive polymer layer and an electrolyte. [Background technology]

[0002] Electrolytic capacitors having an anode body with a dielectric layer and a conductive polymer layer formed so as to cover at least a portion of the dielectric layer are considered to be promising as small-sized, large-capacity, and low ESR (Equivalent Series Resistance) capacitors.

[0003] Patent Document 1 proposes an electrolytic capacitor in which an electrolytic solution is impregnated into a capacitor element including an anode foil having a dielectric layer formed thereon, a cathode foil, a separator interposed between the anode foil and the cathode foil, and a conductive polymer layer formed on the surfaces of the dielectric layer, the separator, and the cathode foil.

[0004] Patent Document 2 proposes forming an intervening layer containing aluminum carbide between aluminum and a carbon-containing layer formed on the surface of the aluminum in the cathode of a solid electrolytic capacitor in order to improve adhesion. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-010657 A [Patent Document 2] JP 2006-100478 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the solid electrolytic capacitor of Patent Document 2, a carbon-containing layer is provided on the cathode in order to increase the capacity, and it is expected that the improved conductivity of the cathode will lower the ESR. In addition, in an electrolytic capacitor using an electrolytic solution as in Patent Document 1, defects in the dielectric layer formed on the anode are easily repaired, so that an increase in leakage current and a decrease in withstand voltage can be suppressed. However, in reality, even if a capacitor element having a carbon-containing layer formed on the cathode is combined with an electrolytic solution, there are cases where sufficient repairability is not obtained, and it is difficult to ensure sufficient adhesion of the carbon-containing layer, which may result in an increase in leakage current and ESR.

[0007] An object of the present invention is to ensure high capacitance and reduce leakage current while suppressing an increase in ESR in an electrolytic capacitor that uses an electrolyte. [Means for solving the problem]

[0008] An example of an electrolytic capacitor according to the present invention includes: A capacitor element and an electrolyte impregnated in the capacitor element, The capacitor element is an anode foil having a dielectric layer formed on a surface thereof; A cathode foil facing the anode foil; a conductive polymer layer interposed between the anode foil and the cathode foil; An inorganic conductive layer is formed on the surface of the cathode foil, the inorganic conductive layer has a convex portion and a concave portion on a surface thereof, a first region in which the inorganic conductive layer and the conductive polymer layer are in contact with each other is formed on the protruding portion; a second region in which the electrolytic solution is contained between the inorganic conductive layer and the conductive polymer layer is formed on the recess; The electrolytic solution contains a first solvent and 0.1 to 6.0 mass % of water, The first solvent has no boiling point or a boiling point of 180° C. or higher; The inorganic conductive layer contains at least one conductive material selected from the group consisting of conductive carbon, nickel, a conductive nickel alloy, a conductive nickel compound, titanium, a conductive titanium alloy, and a conductive titanium compound. Another example of the electrolytic capacitor according to the present invention is A capacitor element and an electrolyte impregnated in the capacitor element, The capacitor element is an anode foil having a dielectric layer formed on a surface thereof; A cathode foil facing the anode foil; a conductive polymer layer interposed between the anode foil and the cathode foil; An inorganic conductive layer is formed on the surface of the cathode foil, the inorganic conductive layer has a convex portion and a concave portion on a surface thereof, a first region in which the inorganic conductive layer and the conductive polymer layer are in contact with each other is formed on the protruding portion; a second region in which the electrolytic solution is contained between the inorganic conductive layer and the conductive polymer layer is formed on the recess; The electrolytic solution contains a first solvent and 0.1 to 6.0 mass % of water, The first solvent has no boiling point or has a boiling point of 180° C. or higher. This specification discloses the following examples as other examples of electrolytic capacitors. [Example 1] The capacitor element and the electrolyte are provided. The capacitor element is an anode foil having a dielectric layer formed thereon; a cathode foil facing the anode foil and having an inorganic conductive layer formed thereon; a conductive polymer layer interposed between the anode foil and the cathode foil and including a conductive polymer; the cathode foil has a roughened surface, and the inorganic conductive layer is formed on the roughened surface; The electrolytic capacitor, wherein the water content of the electrolytic solution is 0.1 to 6.0% by mass. [Example 2] The electrolytic capacitor of Example 1, wherein the conductive polymer layer is formed using a dispersion containing the conductive polymer or a solution containing the conductive polymer. [Example 3] The surface expansion ratio of the cathode foil is 1.5 to 500 cm 2 / cm 2 The electrolytic capacitor according to Example 1 or 2, [Example 4] 4. The electrolytic capacitor according to any one of Examples 1 to 3, wherein the surface of the cathode foil is roughened by etching. [Example 5] The electrolytic capacitor according to any one of Examples 1 to 4, wherein a first region in which the inorganic conductive layer and the conductive polymer layer are in contact with each other and a second region in which the inorganic conductive layer and the conductive polymer layer are not in contact with each other are formed on the surface of the inorganic conductive layer. [Example 6] The electrolytic capacitor according to any one of Examples 1 to 5, wherein the electrolytic solution contains a first solvent that has no boiling point or has a boiling point of 180° C. or higher. [Example 7] 7. The electrolytic capacitor of Example 6, wherein the first solvent comprises a polyol. [Example 8] The electrolytic capacitor according to Example 6 or 7, wherein the amount of the first solvent contained in the electrolytic solution is 3 to 90 mass %. Effect of the Invention

[0009] According to the present invention, in an electrolytic capacitor including a conductive polymer layer, it is possible to achieve low ESR and low leakage current while maintaining high capacitance. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention. [Diagram 2] 2 is a schematic diagram for explaining the configuration of a capacitor element in the electrolytic capacitor of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the electrolytic capacitor of the present invention will be described with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiments. <Electrolytic capacitor> Fig. 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention, and Fig. 2 is a schematic exploded view of a portion of a capacitor element included in the electrolytic capacitor.

[0012] 1, the electrolytic capacitor includes a capacitor element 10 and is housed in an exterior case (specifically, a bottomed case 11) together with an electrolyte (not shown). The exterior case includes bottomed case 11 that houses capacitor element 10 therein, an insulating sealing member 12 that closes the opening of bottomed case 11, and a seat plate 13 that covers sealing member 12. The vicinity of the open end of bottomed case 11 is drawn inward, and the open end is curled so as to be crimped to sealing member 12.

[0013] As shown in Fig. 2, capacitor element 10 includes anode foil 21 connected to lead tab 15A, cathode foil 22 connected to lead tab 15B, and separator 23. Anode foil 21 and cathode foil 22 are wound with separator 23 interposed therebetween, and such capacitor element 10 is also called a wound body. The outermost periphery of capacitor element 10 is fixed by a stop tape 24. Note that Fig. 2 shows a partially unfolded state of capacitor element 10 before the outermost periphery is fixed.

[0014] In the capacitor element 10, the anode foil 21 is a metal foil whose surface is roughened to have irregularities, and a dielectric layer is formed on the metal foil having irregularities. The cathode foil 22 facing the anode foil 21 is a metal foil whose surface is roughened to have irregularities, and an inorganic conductive layer is formed on the metal foil having irregularities. A conductive polymer is attached to at least a part of the surface of the dielectric layer on the anode foil 21 and at least a part of the surface of the inorganic conductive layer on the cathode foil 22 to form a conductive polymer layer, but this is not limited to this case, and the conductive polymer may be attached to any position between the anode foil 21 and the cathode foil 22. For example, the conductive polymer may cover at least a part of the surface of the dielectric layer formed on the anode foil 21, and further cover at least a part of the surface of the inorganic conductive layer on the cathode foil 22 and / or at least a part of the surface of the separator 23.

[0015] In this manner, a conductive polymer layer is formed between anode foil 21 and cathode foil 22. In an electrolytic capacitor, the conductive polymer (specifically, a coating containing a conductive polymer) that covers at least a portion of the surface of the anode foil, cathode foil, separator, etc. is generally sometimes referred to as a solid electrolyte layer (or conductive polymer layer).

[0016] The configuration of the electrolytic capacitor according to the embodiment of the present invention will be described in more detail below.

[0017] The capacitor element includes an anode foil having a dielectric layer formed thereon, a cathode foil having an inorganic conductive layer formed on a roughened surface thereof, and a conductive polymer layer interposed between the anode foil and the cathode foil. The capacitor element may include a separator as necessary. (Capacitor element) (anode foil) The anode foil may be, for example, a metal foil having a roughened surface. The type of metal constituting the metal foil is not particularly limited, but it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal, in terms of ease of forming a dielectric layer.

[0018] The metal foil surface can be roughened by a known method. By roughening, a plurality of projections and recesses are formed on the surface of the metal foil. The roughening is preferably performed, for example, by etching the metal foil. The etching may be performed, for example, by DC electrolysis or AC electrolysis.

[0019] (Dielectric layer) The dielectric layer is formed on the surface of the anode foil. Specifically, since the dielectric layer is formed on the surface of the roughened metal foil, the dielectric layer is formed along the inner wall surfaces of the holes and depressions (pits) on the surface of the anode foil.

[0020] The method for forming the dielectric layer is not particularly limited, but the dielectric layer can be formed by subjecting a metal foil to a chemical conversion treatment. The chemical conversion treatment may be performed, for example, by immersing the metal foil in a chemical conversion solution such as an ammonium adipate solution. In the chemical conversion treatment, a voltage may be applied to the metal foil while it is immersed in the chemical conversion solution, if necessary.

[0021] Usually, from the viewpoint of mass production, a metal foil made of a large valve metal or the like is subjected to a surface roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut to a desired size to prepare an anode foil 21 having a dielectric layer formed thereon.

[0022] (cathode foil) A metal foil may be used for the cathode foil 22. Although there is no particular limitation on the type of metal, it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal.

[0023] In the present invention, a conductive polymer layer is formed using a dispersion in which fine particles of a conductive polymer are dispersed in a dispersion medium or a solution in which a conductive polymer is dissolved in a solvent. Such a conductive polymer layer is formed by contacting the dispersion or solution with an anode foil and a cathode foil, so that the conductive polymer adheres to the periphery of the anode foil and the cathode foil. Although such a conductive polymer layer is homogeneous, highly flexible, and has excellent electrolyte retention, the adhesion between the conductive polymer layer and the anode foil or the cathode foil (or the inorganic conductive layer on the surface) is low. In particular, when an electrolyte is used, the electrolyte permeates between the conductive polymer layer and the inorganic conductive layer, which tends to hinder the contact between the conductive polymer layer and the inorganic conductive layer, making it difficult to increase the capacity and reduce the ESR.

[0024] In the present invention, the surface of the cathode foil is roughened and an inorganic conductive layer is formed on the roughened surface, thereby improving the adhesion between the conductive polymer layer and the inorganic conductive layer, even though the conductive polymer layer is formed using a dispersion or a solution. Specifically, by forming an inorganic conductive layer on the roughened surface of the cathode foil, unevenness is also formed on the surface of the inorganic conductive layer that contacts the conductive polymer layer. In the convex parts of the surface of the inorganic conductive layer, a first region is formed in which the inorganic conductive layer and the conductive polymer layer are in contact, and in the concave parts, a second region is formed in which the inorganic conductive layer and the conductive polymer layer are not in contact. In the second region, a gap is formed between the inorganic conductive layer and the conductive polymer layer, so that even if an electrolyte permeates between the inorganic conductive layer and the conductive polymer layer, it flows into this gap. Therefore, in the first region, the electrolyte is suppressed from entering between the conductive polymer layer and the inorganic conductive layer, or the amount of electrolyte that enters or remains between the layers is reduced. As a result, a high contact pressure can be ensured, and a decrease in the adhesion between the conductive polymer layer and the inorganic conductive layer can be suppressed, while an increase in the resistance at the interface can be suppressed.

[0025] The degree of roughening of the cathode foil surface can be expressed by the surface expansion ratio. The surface expansion ratio of the cathode foil surface is, for example, 1.3 to 550 cm 2 / cm 2 and 1.5 to 500 cm 2 / cm 2is preferable, and 2 to 120 cm 2 / cm 2 It is more preferable that the surface expansion ratio is within such a range. Since the first region and the second region are formed in a well-balanced manner, it is easy to ensure high adhesion between the conductive polymer layer and the inorganic conductive layer. In addition, it is easy to prevent moisture, by-products, gas, etc. from adhering to or being adsorbed on the cathode foil surface before the inorganic conductive layer is formed. As a result, a more homogeneous inorganic conductive layer is easily formed, and from this viewpoint, it is easy to prevent a decrease in adhesion. When the surface expansion ratio is within such a range, it is easy to prevent a decrease in adhesion between the conductive polymer layer and the inorganic conductive layer. 2 / cm 2 In this case, the decrease in adhesion can be further suppressed, and therefore the decrease in capacity and the increase in ESR during long-term use can be suppressed.

[0026] The surface of the cathode foil can be roughened by a known method, for example, by etching. The etching treatment may be performed by, for example, a direct current electrolysis method or an alternating current electrolysis method. From the viewpoint of easily securing a high capacity even when charging and discharging are repeated, it is preferable to roughen the surface by etching.

[0027] (Inorganic conductive layer) The inorganic conductive layer is desirably formed as a whole from an inorganic material having electrical conductivity, and is distinguished from a conductive polymer layer formed from an organic material.

[0028] Examples of conductive inorganic materials forming the inorganic conductive layer include conductive carbon, metals, and conductive metal compounds. Examples of conductive carbon include amorphous carbon, carbon black such as acetylene black, soft carbon, hard carbon, graphite, and carbon fibers such as carbon nanotubes. Metals and metal compounds that are unlikely to form a passive film due to contact with air are preferred. Examples of metals include titanium, titanium alloys, nickel, and nickel alloys. Examples of metal compounds include nitrides and carbides, and nitrides are preferred. Examples of metals constituting metal compounds include titanium and / or nickel. The inorganic conductive layer may contain one or more of these inorganic materials.

[0029] The inorganic conductive layer may contain the above-mentioned conductive inorganic material and a binder, but it is preferable that the proportion of the conductive inorganic material is as high as possible. The amount of the conductive inorganic material in the inorganic conductive layer is preferably, for example, 95 mass % or more or 99 mass % or more. The inorganic conductive layer may also be a layer made of the above-mentioned conductive inorganic material. The inorganic conductive layer may be formed by forming a layer containing a conductive inorganic material and a binder and removing the binder by heat treatment. In particular, the inorganic conductive layer is preferably a deposited film of a conductive inorganic material (particularly, conductive carbon such as amorphous carbon).

[0030] Even when the cathode foil and the inorganic conductive layer are formed of the same material, the cathode foil and the inorganic conductive layer have different metal distributions (for example, the metal distribution in the inorganic conductive layer is coarser than that in the cathode foil), and therefore the cathode foil and the inorganic conductive layer can be distinguished, for example, in an electron microscope photograph of a cross section.

[0031] From the viewpoint of increasing the adhesion between the inorganic conductive layer and the cathode foil, the inorganic conductive layer may further include a conductive base layer as necessary. The base layer constituting a part of the inorganic conductive layer preferably includes a conductive inorganic material such as a metal or a conductive metal compound, for example, from among the conductive inorganic materials exemplified above. As the metal, titanium is preferable, and as the metal compound, titanium nitride is preferable.

[0032] The inorganic conductive layer may have a thickness of, for example, 1 nm to 10 μm. When the inorganic conductive layer is a deposited film, the inorganic conductive layer may have a thickness of, for example, 1 nm to 100 nm, and when the inorganic conductive layer is formed from a layer containing a conductive inorganic material and a binder, the inorganic conductive layer may have a thickness of, for example, 100 nm to 10 μm. The thickness of the inorganic conductive layer may be an average thickness obtained by averaging thicknesses measured at multiple points (for example, 10 points) in a cross-sectional image.

[0033] When the thickness of the inorganic conductive layer is within the above range, it is easy to prevent a decrease in adhesion between the inorganic conductive layer and the conductive polymer layer, and it is easy to ensure high conductivity.

[0034] (Separator) Separator 23 may be made of, for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (for example, aliphatic polyamide, aromatic polyamide such as aramid).

[0035] The capacitor element 10 can be produced by a known method. For example, the capacitor element 10 may be produced by stacking an anode foil 21 having a dielectric layer formed thereon and a cathode foil 22 having an inorganic conductive layer formed thereon with a separator 23 interposed therebetween, and then forming a conductive polymer layer between the anode foil 21 and the cathode foil 22. The capacitor element 10 may be produced by winding the anode foil 21 having a dielectric layer formed thereon and the cathode foil 22 having an inorganic conductive layer formed thereon with the separator 23 interposed therebetween to form a wound body as shown in FIG. 2, and forming a conductive polymer layer between the anode foil 21 and the cathode foil 22. When forming the wound body, the lead tabs 15A and 15B may be wound while being wound, so that the lead tabs 15A and 15B are planted from the wound body as shown in FIG. 2.

[0036] The material of the lead tabs 15A and 15B is not particularly limited as long as it is a conductive material. The surfaces of the lead tabs 15A and 15B may be subjected to a chemical conversion treatment. Furthermore, the portions of the lead tabs 15A and 15B that contact the sealing member 12 and the portions connected to the lead wires 14A and 14B may be covered with a resin material.

[0037] The material of the lead wires 14A, 14B connected to the lead tabs 15A, 15B, respectively, is not particularly limited, and may be a conductive material or the like.

[0038] Of anode foil 21, cathode foil 22, and separator 23, the one located in the outermost layer of the wound body (cathode foil 22 in FIG. 2) has an edge of the outer surface fixed with stop tape 24. When anode foil 21 is prepared by cutting a large metal foil, a chemical conversion treatment may be further performed on the capacitor element in the wound body, in order to provide a dielectric layer on the cut surface of anode foil 21.

[0039] (Conductive polymer layer) The conductive polymer layer is interposed between the anode foil 21 and the cathode foil 22. The conductive polymer layer is preferably formed on at least a portion of the surface of the dielectric layer formed on the surface of the anode foil 21 so as to cover the dielectric layer, and more preferably formed so as to cover as much of the dielectric layer as possible. The conductive polymer layer is preferably formed on at least a portion of the surface of the inorganic conductive layer formed on the surface of the cathode foil 22 so as to cover the inorganic conductive layer, and more preferably formed so as to cover as much of the inorganic conductive layer as possible. When the capacitor element includes a separator, the conductive polymer layer may be formed not only on the surfaces of the dielectric layer and the inorganic conductive layer, but also on the surface of the separator.

[0040] When the conductive polymer layer is formed using a dispersion in which conductive polymer particles are dispersed in a dispersion medium, it is preferable to make the diameter of the conductive polymer particles smaller than the diameter of the recesses on the roughened surface of the cathode foil. In this way, the conductive polymer particles also adhere to the surface of the inorganic conductive layer in the recesses, thereby further reducing the ESR of the electrolytic capacitor.

[0041] (conductive polymer) Examples of the conductive polymer contained in the conductive polymer layer include polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. These may be used alone or in combination of two or more kinds, or may be copolymers of two or more kinds of monomers.

[0042] In this specification, polypyrrole, polythiophene, polyfuran, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyfuran, polyaniline, etc. as their basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyfuran, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene), etc.

[0043] The conductive polymer may be used alone or in combination of two or more kinds.

[0044] The weight average molecular weight of the conductive polymer is not particularly limited, but is, for example, 1000 to 1,000,000.

[0045] (Dopant) The conductive polymer layer may contain a dopant. The dopant may be contained in the conductive polymer layer in a state where it is doped into the conductive polymer, or may be contained in the conductive polymer layer in a state where it is bonded to the conductive polymer.

[0046] As the dopant, a polyanion can be used. Specific examples of the polyanion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. Among them, polyanions derived from polystyrene sulfonic acid are preferred. These may be used alone or in combination of two or more. These may also be polymers of a single monomer or copolymers of two or more monomers.

[0047] The weight-average molecular weight of the polyanion is not particularly limited, but is, for example, 1,000 to 1,000,000. A conductive polymer containing such a polyanion is likely to be uniformly dispersed in a solvent, and is likely to be uniformly attached to the surface of a dielectric layer or an inorganic conductive layer.

[0048] (electrolyte) In general, in solid electrolytic capacitors, forming a conductive carbon layer on the surface of the cathode foil is expected to increase the capacity. On the other hand, using an electrolyte solution increases the repairability of the dielectric layer and suppresses leakage current. However, since it is difficult to suppress the generation of capacitance in the cathode when the carbon layer is combined with the electrolyte solution, it has been thought that it is difficult to actually increase the capacity by combining the carbon layer with the electrolyte solution. In fact, when the carbon layer is combined with the electrolyte solution, there are cases where the repairability of the dielectric layer cannot be sufficiently obtained.

[0049] However, in practice, when a cathode foil having a conductive layer including a carbon layer is combined with an electrolyte, the moisture content of the electrolyte can be set to 0.1 mass % or more to obtain a repair effect on the dielectric layer, thereby reducing leakage current.

[0050] On the other hand, when the electrolyte contains moisture, the capacitance decreases and the ESR increases as the electrolytic capacitor is used for a certain period of time. This is believed to be due to the moisture in the electrolyte reducing the adhesion between the cathode foil and the conductive layer including the carbon layer. In addition, when an electrolyte containing moisture is used and the conductive polymer layer is formed by polymerizing a conductive polymer precursor in contact with the cathode foil, the remaining oxidizing agent and precursor become active due to the action of moisture in the electrolyte, causing corrosion of the foil and reducing the adhesion between the cathode foil and the conductive layer, and between the anode foil or the conductive layer and the conductive polymer layer.

[0051] In this embodiment, the conductive polymer layer is formed using a dispersion or solution containing a conductive polymer, and the moisture content in the electrolyte is set to 6.0 mass % or less, thereby preventing a decrease in adhesion between the cathode foil and the conductive layer, and between the anode foil or the conductive layer and the conductive polymer layer, and thus preventing an increase in ESR while maintaining a high capacity.

[0052] If the moisture content in the electrolyte is less than 0.1% by mass, the dielectric layer is poorly restored, and leakage current cannot be suppressed. If the moisture content exceeds 6.0% by mass, ESR increases. Thus, in this embodiment, it is important to set the moisture content in the electrolyte to 0.1% by mass or more and 6.0% by mass or less. From the viewpoint of stably reducing ESR, the moisture content in the electrolyte is preferably 5.0% by mass or less. From the viewpoint of further reducing leakage current, the moisture content in the electrolyte is preferably 0.5% by mass or more, and more preferably 1.0% by mass or more. These lower and upper limits can be combined arbitrarily. The moisture content in the electrolyte may be, for example, 0.1 to 5.0% by mass or 0.5 to 5.0% by mass.

[0053] The moisture in the electrolytic solution does not necessarily have to be contained in the electrolytic solution used when assembling the electrolytic capacitor, and may be mixed into the electrolytic solution during the process of assembling the electrolytic capacitor. For example, the moisture may be contained in the components of the electrolytic capacitor beforehand, or may be contained in a dispersion or solution containing a conductive polymer.

[0054] The electrolyte is not particularly limited as long as it has the above-mentioned water content, and a non-aqueous solvent may be used, or a solution containing a non-aqueous solvent and an ionic substance (solute) dissolved in the non-aqueous solvent may be used. Note that the non-aqueous solvent is a general term for liquids other than water and liquids containing water, and includes organic solvents and ionic liquids.

[0055] Examples of non-aqueous solvents include polyols (alkylene glycols such as ethylene glycol and propylene glycol; polyalkylene glycols such as polyethylene glycol; glycerins such as glycerin and polyglycerin), cyclic sulfones such as sulfolane, lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, formaldehyde, etc. The non-aqueous solvents may be used alone or in combination of two or more.

[0056] The electrolytic solution preferably contains at least a solvent (first solvent) that has no boiling point or has a high boiling point (for example, 180° C. or higher) among the nonaqueous solvents. When the electrolytic solution contains the first solvent, the electrolytic solution can be prevented from running out even when the electrolytic capacitor is used for a long period of time, so that high reliability can be ensured for a long period of time. However, when the electrolytic solution contains the first solvent, it is likely to penetrate between the conductive polymer layer and the inorganic conductive layer during repeated charging and discharging, and to impair the adhesion between the two layers. In particular, when a cathode foil that is not roughened is used, if an electrolytic solution containing the first solvent is used, the adhesion between the conductive polymer layer and the inorganic conductive layer is low, and the conductivity is low, so that the capacity cannot be ensured and the ESR cannot be reduced. In the present invention, since an inorganic conductive layer is formed on the roughened surface of the cathode foil, high adhesion between the conductive polymer layer and the inorganic conductive layer can be ensured even when the electrolytic solution contains the first solvent.

[0057] The boiling point of the first solvent may be 180° C. or higher, and may be 200° C. or higher. As the first solvent, polyol is preferable. Although polyethylene glycol, polyglycerin, and the like may not have a boiling point depending on the molecular weight, such compounds (but are liquid) are also preferable as the first solvent.

[0058] The first solvent does not necessarily have to be contained in the electrolytic solution used when assembling the electrolytic capacitor, and may be contained in the treatment solution used in the process of assembling the electrolytic capacitor. For example, a dispersion or solution containing a conductive polymer may contain the first solvent. From the viewpoint of easily ensuring the adhesion between the conductive polymer layer and the cathode foil, the amount of the first solvent contained in the dispersion or solution is preferably 50 mass % or less of the dispersion or solution. The first solvent has no boiling point or a high boiling point, and therefore remains in the assembled electrolytic capacitor. The remaining first solvent seeps into the electrolytic solution contained in the electrolytic capacitor, so that the electrolytic solution in the electrolytic capacitor contains the first solvent.

[0059] The amount of the first solvent contained in the electrolytic solution is, for example, 3 to 95 mass %, and preferably 10 to 80 mass %. The amount of the first solvent contained in the electrolytic solution may be 10 to 30 mass %. When the amount of the first solvent is within such a range, a decrease in adhesion between the conductive polymer layer and the inorganic conductive layer is suppressed.

[0060] The solute contained in the electrolytic solution may be a salt of an anion or a cation, and preferably an organic salt in which at least one of the anion and the cation is an organic substance. Examples of the organic salt include trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, and mono-1,3-dimethyl-2-ethylimidazolinium phthalate. The solute may be used alone or in combination of two or more kinds.

[0061] In the electrolytic capacitor of the present invention having a solid electrolyte layer made of a conductive polymer layer, an organic solvent that does not contain an ionic substance (solute) may be used as the electrolyte. <Manufacturing method of electrolytic capacitors> Hereinafter, an example of a method for manufacturing an electrolytic capacitor according to an embodiment of the present invention will be described step by step.

[0062] The electrolytic capacitor can be obtained through the steps of preparing a dispersion or solution (first treatment liquid) containing a conductive polymer (first step), preparing an anode foil with a dielectric layer (second step), preparing a cathode foil with an inorganic conductive layer (third step), impregnating the anode foil, cathode foil, and a separator interposed between the anode foil and cathode foil as necessary with the first treatment liquid to obtain a capacitor element (fourth step), and impregnating the capacitor element with an electrolytic solution (fifth step). Through the fourth step, a conductive polymer layer can be formed. The solvent component may be removed at an appropriate stage. (i) First step In the first step, a first processing liquid containing a conductive polymer (and a dopant) and a solvent (second solvent) is prepared.

[0063] The first treatment liquid can be obtained, for example, by dispersing or dissolving the conductive polymer (and the dopant) in the second solvent. The first treatment liquid can also be obtained, for example, by polymerizing the raw material of the conductive polymer (for example, a precursor such as a monomer and / or oligomer of the conductive polymer) in the presence of the dopant in the second solvent. When preparing the first treatment liquid by polymerization, unreacted raw materials and by-products may be removed as necessary. Alternatively, after polymerization is performed using a part of the second solvent, the remainder of the second solvent may be added to the obtained mixture.

[0064] The second solvent is not particularly limited and may be water or a non-aqueous solvent (organic solvent, ionic liquid, etc.). Among them, the second solvent is preferably a polar solvent. The polar solvent may be a protic solvent or an aprotic solvent.

[0065] Examples of protic solvents include monohydric alcohols (methanol, ethanol, propanol, butanol, etc.), polyols (alkylene glycols such as ethylene glycol and propylene glycol; polyalkylene glycols such as polyethylene glycol; glycerins such as glycerin and polyglycerin, etc.), glycol monoethers such as diethylene glycol monobutyl ether, formaldehyde, and water.

[0066] Examples of aprotic solvents include amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, ketones such as methyl ethyl ketone and γ-butyrolactone, ethers (e.g., cyclic ethers) such as 1,4-dioxane, sulfones such as dimethyl sulfoxide and sulfolane, and carbonate compounds (e.g., cyclic carbonates) such as propylene carbonate.

[0067] Among them, the second solvent is preferably a protic solvent. From the viewpoint of improving the handleability of the first treatment liquid and the dispersibility of the conductive polymer, it is preferable that the second solvent contains water. When the second solvent contains a polyol, the conductivity of the conductive polymer layer is easily increased (that is, the ESR is easily reduced). Therefore, it is also preferable that the second solvent contains a polyol, and it is also preferable to use a second solvent containing at least water and a polyol.

[0068] The first treatment liquid is preferably a dispersion in which the conductive polymer (and dopant) is dispersed in the second solvent. In the dispersion, the conductive polymer and / or dopant are preferably in the form of particles (or powder). The average particle size of the particles dispersed in the dispersion is preferably 5 to 100 nm. The average particle size can be determined, for example, from the particle size distribution by dynamic light scattering.

[0069] The amount of the dopant contained in the first treatment liquid is preferably 10 to 1000 parts by mass, and more preferably 50 to 200 parts by mass, relative to 100 parts by mass of the conductive polymer.

[0070] The concentration of the conductive polymer (including a dopant or a polyanion) in the first treatment liquid is preferably 0.5 to 3 mass %. The first treatment liquid with such a concentration is suitable for attaching an appropriate amount of the conductive polymer and is easy to be impregnated, which is advantageous in terms of improving productivity.

[0071] The first treatment liquid may contain an electrolyte, a known additive, and the like, as necessary. (ii) Second step In the second step, as described above, the surface of the anode foil is subjected to, for example, chemical conversion treatment to form a dielectric layer on the surface of the anode foil. (iii) Third step In the third step, a cathode foil having an inorganic conductive layer formed on its surface is prepared.

[0072] The inorganic conductive layer can be formed by attaching a powdered conductive inorganic material to the surface of the cathode foil, or by a method such as vacuum deposition, etc. The inorganic conductive layer may also be formed by applying a paste or slurry containing a conductive inorganic material and a binder to the surface of the cathode foil to form a coating film and drying the coating film, or by heat-treating the coating film to remove the binder.

[0073] An inorganic conductive layer including a deposited film of a conductive inorganic material (particularly, conductive carbon such as amorphous carbon) can be formed by depositing the above-mentioned inorganic material on the surface of the cathode foil using a gas phase method such as chemical vapor deposition, vacuum deposition, sputtering, ion plating, etc. For example, an inorganic conductive layer including a metal nitride may be formed by carrying out a gas phase method in a nitrogen gas atmosphere.

[0074] In the third step, if necessary, a base layer may be formed on the surface of the cathode foil, and a layer containing a conductive inorganic material may be formed on the base layer as described above to form an inorganic conductive layer. The base layer constituting the inorganic conductive layer can be formed in the same manner as described above using a conductive inorganic material such as a metal or a conductive compound. The base layer is preferably formed by depositing a conductive inorganic material on the surface of the cathode foil using a vapor phase method. (iv) 4th step In the fourth step, the anode foil on which the dielectric layer is formed, the cathode foil on which the inorganic conductive layer is formed, and the separator, if necessary, are impregnated with the first treatment liquid. More specifically, in the fourth step, the anode foil on which the dielectric layer is formed and the cathode foil on which the inorganic conductive layer is formed are wound with a separator interposed therebetween, and the first treatment liquid may be impregnated into the wound body. The impregnation with the first treatment liquid may be performed by immersing the wound body in the first treatment liquid, or by injecting the first treatment liquid into the wound body. The inorganic conductive layer can be formed by roughening the cathode foil and depositing a conductive inorganic material on the roughened surface of the cathode foil by a vapor phase method.

[0075] The impregnation with the first treatment liquid may be performed under atmospheric pressure, or under reduced pressure, for example, 10 to 100 kPa, preferably 40 to 100 kPa. The impregnation may be performed under ultrasonic vibration, if necessary. The impregnation time depends on the size of the capacitor element 10, but is, for example, 1 second to 5 hours, preferably 1 minute to 30 minutes.

[0076] After the anode foil and the cathode foil (and the separator) are impregnated with the first treatment solution, they may be dried as necessary. At least a part of the second solvent is removed by drying. Drying may be performed under heating, and may be performed under reduced pressure as necessary.

[0077] In this manner, through the fourth step, a conductive polymer layer is formed between the anode foil and the cathode foil, thereby forming capacitor element 10.

[0078] When the second solvent contains a non-aqueous solvent (organic solvent), the non-aqueous solvent may be left in the capacitor element 10 after the conductive polymer layer is formed to serve as the electrolyte. In this case, the fifth step of impregnating the electrolyte, which will be described later, may be performed or may be omitted. (v) Fifth Step In the fifth step, the capacitor element obtained in the fourth step is impregnated with an electrolyte.

[0079] Impregnation of the electrolyte into the capacitor element 10 is not particularly limited and can be performed by a known method. For example, the capacitor element 10 may be immersed in the electrolyte, or the electrolyte may be poured into a container containing the capacitor element 10. The impregnation of the electrolyte into the capacitor element 10 may be performed under reduced pressure (for example, 10 to 100 kPa) as necessary. (others) Capacitor element 10 may be sealed. More specifically, capacitor element 10 is first housed in bottomed case 11 such that lead wires 14A and 14B are located on the open upper surface of bottomed case 11. The material of bottomed case 11 may be a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.

[0080] Next, sealing member 12, which is formed so that lead wires 14A and 14B pass through it, is placed above capacitor element 10, and capacitor element 10 is sealed within bottomed case 11. Sealing member 12 may be made of an insulating material. As the insulating material, an elastic body is preferable, and among them, silicone rubber, fluororubber, ethylene propylene rubber, chlorosulfonated polyethylene rubber (such as Hypalon rubber), butyl rubber, isoprene rubber, and the like, which have high heat resistance, are preferable.

[0081] Next, a horizontal drawing process is performed near the open end of bottomed case 11, and the open end is curled by crimping it to sealing member 12. Then, seat plate 13 is placed on the curled portion to complete the electrolytic capacitor as shown in Fig. 1. After that, an aging process may be performed while applying the rated voltage.

[0082] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, such as a chip-type electrolytic capacitor that uses a metal sintered body instead of an anode foil, or a laminate-type electrolytic capacitor that uses a metal plate instead of an anode foil. EXAMPLES

[0083] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples. Example 1 Wound electrolytic capacitors having a rated voltage of 35 V and a rated capacitance of 47 μF (except for Comparative Example 10) as shown in FIG. 1 were fabricated according to the following procedure and evaluated. (1) Manufacturing of electrolytic capacitors (Preparation of anode foil with dielectric layer) An aluminum foil having a thickness of 100 μm was subjected to an etching treatment to roughen the surface of the aluminum foil, and then a dielectric layer was formed on the surface of the aluminum foil by a chemical conversion treatment using an aqueous solution of ammonium adipate, thereby preparing an anode foil having a dielectric layer.

[0084] (Preparation of cathode foil having inorganic conductive layer) A cathode foil having an inorganic conductive layer formed on the surface of the cathode foil was prepared. The cathode foil had a surface roughened by etching and a surface area of ​​1.5 cm2. 2 / cm 2 An aluminum foil (thickness: 30 μm) was used. An inorganic conductive layer was formed on the surface of the cathode foil by ion plating of conductive carbon. The thickness of the inorganic conductive layer was 8 nm.

[0085] (Making of the roll) Anode lead tabs and cathode lead tabs were connected to the anode foil and cathode foil, and the anode foil and cathode foil were wound with a separator interposed therebetween while the lead tabs were rolled up to obtain a wound body. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. The wound body was then subjected to a chemical conversion treatment again to form a dielectric layer on the cut ends of the anode foil. Next, the ends of the outer surface of the wound body were fixed with a winding stop tape.

[0086] (Preparation of first treatment liquid) A mixed solution was prepared by dissolving 3,4-ethylenedioxythiophene and polystyrenesulfonic acid as a dopant in ion-exchanged water. While stirring the obtained solution, ferric sulfate and sodium persulfate (oxidizing agent) dissolved in ion-exchanged water were added to carry out a polymerization reaction. After the reaction, the obtained reaction solution was dialyzed to remove unreacted monomers and excess oxidizing agent, and a dispersion containing poly3,4-ethylenedioxythiophene doped with polystyrenesulfonic acid (PEDOT-PSS) was obtained. The concentration of PEDOT-PSS in the dispersion was about 2 mass%, and the mass ratio of PSS to PEDOT (=PSS:PEDOT) was about 2:1. A first treatment liquid in the form of a dispersion was prepared by adding 5 mass% ethylene glycol (second solvent) to the obtained dispersion and stirring it.

[0087] (Impregnation of first treatment liquid) The wound body was impregnated with the first treatment solution for 5 minutes. The wound body was then heated at 150° C. for 20 minutes to remove the solvent. In this manner, a capacitor element was produced in which a conductive polymer layer was formed between the anode foil and the cathode foil.

[0088] (Electrolyte Impregnation) The capacitor element was then impregnated with an electrolyte under reduced pressure. A solution containing γBL:glycerin:mono(ethyldimethylamine)phthalate (solute) = 50:25:25 (mass ratio) was used as the electrolyte. The amount of moisture contained in the γBL and glycerin used was measured in advance, and the amount of moisture in the electrolyte was adjusted by adding water to the electrolyte or evaporating the moisture by heating so that the amount of moisture in the electrolyte reached the desired amount. In the electrolyte, γBL and glycerin were the first solvents. (Sealing of capacitor elements) The capacitor element impregnated with the electrolytic solution was housed in an exterior case as shown in Figure 1 and sealed to produce an electrolytic capacitor. A total of 300 electrolytic capacitors were produced in the same manner. (2) Performance evaluation (a) Moisture content The electrolyte was removed from the assembled electrolytic capacitor, and the moisture content (mass %) in the electrolyte was measured by the Karl Fischer method, which revealed that the moisture content in the electrolyte was 0.10 mass %.

[0089] (b) Capacitance and ESR value The initial characteristics of the electrolytic capacitor were measured: capacitance (μF) and ESR value (mΩ). Specifically, the initial capacitance (μF) of the electrolytic capacitor was measured at a frequency of 120 Hz using an LCR meter for four-terminal measurement. In addition, the ESR value (mΩ) of the electrolytic capacitor was measured at a frequency of 100 kHz using an LCR meter for four-terminal measurement.

[0090] The capacitance (μF) and ESR value (mΩ) after a high-temperature storage test at 125° C. for 3000 hours were also measured in the same manner as for the initial characteristics described above.

[0091] The capacitance and ESR values ​​were each measured for 120 randomly selected electrolytic capacitors, and the average values ​​were calculated. (c) Leakage current (LC) As the initial characteristics of the electrolytic capacitor, the rated voltage was applied to the electrolytic capacitor and the leakage current (μA) was measured after 2 minutes.

[0092] The leakage current (μA) after a high-temperature storage test at 125° C. for 3000 hours was also measured in the same manner as in the case of the initial characteristics described above.

[0093] (d) Amount of the first solvent in the electrolyte The electrolytic solution was extracted from the electrolytic capacitor, and the amount (mass %) of the first solvent contained in the electrolytic solution was measured by gas chromatography, which revealed that the amount of the first solvent in the electrolytic solution was 76 mass %. Examples 2 to 25 and Comparative Examples 1 to 9 Electrolytic capacitors were prepared and evaluated in the same manner as in Example 1, except that the surface expansion ratio of the cathode foil used and the water content in the electrolyte of the assembled electrolytic capacitor were adjusted to the values ​​shown in Table 1, and in some examples and comparative examples, although not shown in Table 1, the thickness of the cathode foil and the water content in the electrolyte were adjusted. Comparative Example 10 An electrolytic capacitor was fabricated and evaluated in the same manner as in Example 1, except that the surface expansion ratio of the cathode foil and the water content in the electrolyte of the assembled electrolytic capacitor were adjusted so that they were the values ​​shown in Table 1, and that a cathode foil not having an inorganic conductive layer on its surface was used.

[0094] In the electrolytic capacitors assembled in Examples 2 to 25 and Comparative Examples 1 to 10, the amount of the first solvent in the electrolytic solution was 75.1 to 76.0 mass %.

[0095] The results of the Examples and Comparative Examples are shown in Table 1. Examples 1 to 25 are A1 to A25, and Comparative Examples 1 to 10 are B1 to B10.

[0096] [Table 1]

[0097] As shown in Table 1, the cathode foils having an inorganic conductive layer on the surface thereof, such as in Examples 1 to 25 and Comparative Examples 1 to 9, had a higher (initial) capacitance than the cathode foils having no inorganic conductive layer on the surface thereof, such as in Comparative Example 10.

[0098] In Examples 1 to 25, the initial capacity was high, and the initial ESR and initial leakage current were also suppressed to be low. Even after being left at high temperature for 3000 hours, a relatively high capacity was ensured, and the increase in ESR and leakage current was also suppressed. In Comparative Examples 1 to 3, in which the surface of the cathode foil was not roughened, the ESR increased significantly after being left at high temperature for 3000 hours. In Comparative Examples 4, 6, and 7, in which the moisture content of the electrolyte was 0.05%, the leakage current increased significantly after being left at high temperature for 3000 hours. In Comparative Examples 5, 7, and 9, in which the moisture content of the electrolyte was 8%, the ESR increased significantly after being left at high temperature for 3000 hours.

[0099] In addition, in Examples 1 to 5 in which the cathode foil expansion ratio was 1.5%, the ESR of Example 5 in which the moisture content of the electrolyte was 6% after leaving the cathode foil at high temperature for 3000 hours tends to be slightly higher than the ESR of Examples 1 to 4 in which the moisture content of the electrolyte was 5% or less after leaving the cathode foil at high temperature for 3000 hours. However, in Examples 6 to 25, this tendency becomes smaller as the expansion ratio increases, and the ESR of Example 5 in which the moisture content of the electrolyte was 6% after leaving the cathode foil at high temperature for 3000 hours tends to be slightly higher than the ESR of Examples 1 to 4 in which the moisture content of the electrolyte was 5% or less after leaving the cathode foil at high temperature for 3000 hours. 2 / cm 2As described above, the ESR of Example 15, in which the moisture content of the electrolyte was 6%, after being left at high temperature for 3000 hours is at the same level as Examples 10 to 14, in which the moisture content of the electrolyte was 0.1 to 5%. This is because, by roughening the surface of the cathode foil, the adhesion between the inorganic conductive layer formed on the surface of the cathode foil and the conductive polymer layer is improved, suppressing an increase in ESR, and by roughening the surface of the cathode foil, an increase in ESR due to the influence of moisture contained in the electrolyte is suppressed, and it is considered that the allowable range of the moisture content of the electrolyte is expanded by roughening the surface of the cathode foil. [Industrial Applicability]

[0100] The present invention can be used in an electrolytic capacitor including a conductive polymer layer and an electrolyte solution. [Explanation of symbols]

[0101] 10: capacitor element, 11: bottomed case, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead tabs, 21: anode foil, 22: cathode foil, 23: separator, 24: winding stop tape

Claims

1. A capacitor element and an electrolyte impregnated in the capacitor element, The capacitor element is an anode foil having a dielectric layer formed on a surface thereof; A cathode foil facing the anode foil; a conductive polymer layer interposed between the anode foil and the cathode foil; An inorganic conductive layer is formed on the surface of the cathode foil, the inorganic conductive layer has a convex portion and a concave portion on a surface thereof, a first region in which the inorganic conductive layer and the conductive polymer layer are in contact with each other is formed on the protrusion; a second region in which the electrolytic solution is contained between the inorganic conductive layer and the conductive polymer layer is formed on the recess; The electrolyte solution contains a first solvent and 0.1 to 6.0 mass % water, The first solvent has no boiling point or a boiling point of 180° C. or higher; The electrolytic capacitor, wherein the inorganic conductive layer comprises a carbon layer containing conductive carbon.

2. The electrolytic capacitor described in claim 1, wherein the carbon layer further contains at least one conductive material selected from the group consisting of nickel, a conductive nickel alloy, a conductive nickel compound, titanium, a conductive titanium alloy, and a conductive titanium compound.

3. The inorganic conductive layer is formed on a roughened surface of an aluminum foil, The surface expansion ratio of the aluminum foil is 1.5 to 500 cm 2 / cm 2 3. The electrolytic capacitor according to claim 1 or 2,

4. The inorganic conductive layer is formed on a roughened surface of an aluminum foil, The surface expansion ratio of the aluminum foil is 2 to 120 cm 2 / cm 2 3. The electrolytic capacitor according to claim 1 or 2,

5. 5. The electrolytic capacitor according to claim 1, wherein the inorganic conductive layer has a thickness of 1 nm to 10 μm.

6. 6. The electrolytic capacitor according to claim 1, wherein the electrolytic solution contains 0.1 to 5.0 mass % of water.

7. The electrolytic capacitor according to claim 1 , wherein the first solvent includes a polyol.

8. The electrolytic capacitor of claim 7 , wherein the polyol comprises a glycerin.

9. The electrolytic capacitor according to any one of claims 1 to 8, wherein the amount of the first solvent contained in the electrolytic solution is 3 to 90 mass %.

10. The electrolytic capacitor according to any one of claims 1 to 9, wherein the conductive polymer layer contains a polyanion.

Citation Information

Patent Citations

  • Cathode material for electrolytic capacitor

    JP1986180420A

  • Cathode material for electrolytic capacitor

    JP1986214420A

  • Electrolytic capacitor

    JP1993029180A

  • Solid-state electrolytic capacitor

    JP1998270291A

  • Electrolytic capacitor

    JP1999283874A